3. EMANSIPASI KEJAHATAN: STUDI GENDER TERHADAP PEREMPUAN SEBAGAI PELAKU KEJAHATAN NARKOBA TRANSNASIONAL - Fahrizal Lazuardi; Ika Riswanti Putranti; Hermini Susiatiningsih (Journal of International Relations Diponegoro, 2016)
It has been long and common to accept that female are less likely to commit crime thando male. However, some researchers rejected this idea (Adler, 1975; Simon 1975;Steffensmeier & Allan, 1998). They argued that emancipation and gender equality weredecisive factors to explain how and why female with better equality and represent inpreviously male dominated occupations caused a steady increase in the number of crimeover recent years. According to those assumptions, this paper tries to connect the relationbetween emancipation and gender equality with transnational drug crime. This paperdeduces that the higher emancipation and gender equality which female get, the highertransnational drug crime will occurred. But after further testing through mixed methodanalysis, this paper concludes that higher emancipation and gender equality will preciselyreduce the intensity of transnational drug crime by female. Later, this paper alsodiscovers that female with higher emancipation and gender equality actually are thevictim, and so female with lower emancipation and gender equality are the pure doer oftransnational drug crime.